China's Impact on Africa - the Role of Trade, FDI and Aid - Matthias Busse; Ceren Erdogan; Henning Mühlen (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2014)
We investigate the impact of Chinese activities in sub-Saharan African countries with respect to the growth performance of economies in that region. Using a Solow-type growth model and panel data for the period 1991 to 2011, we find that African economies that export natural resources have benefited from positive terms-of-trade effects. In addition, there is evidence for displacement effects of African firms due to competition from China. Chinese foreign investment and aid in Africa does not have an impact on growth.
Keywords: F14; F23; F35; O47; 330; China; Sub-Saharan Africa; Trade; FDI; Foreign aid; Economic growth; South-south cooperation; Auslandsinvestition; Entwicklungshilfe; Chinesisch; Außenwirtschaftspolitik; China; Wirtschaftswachstum; Subsahara-Afrika